KESEJAHTERAAN PSIKOLOGIS TENAGA MEDIS DI MASA PANDEMI - Purnomosidi, Faqih; Rizkila, Adinda (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
This journal reviews the psychological well-being of health workers in dealing with the pandemic period due to the COVID-19 that has attacked almost all countries in the world. This study aims to determine the impact of the Covid-19 virus on the psychological condition of health workers. The sample used is 7 representatives of health workers such as midwives and nurses who work in the city of Surakarta. The sampling technique used in this research is quota sampling with data collection using interview and observation techniques. The type of research in this journal is qualitative research with a naturalist paradigm. The results of this study indicate that health workers have not fully achieved psychological well-being. There are still many of them who feel pressured in carrying out their work. The conclusion that can be drawn from this research is the need for full support from the community for health workers related to their work. If health workers achieve psychological well-being, they can work happily and calmly so that the recovery rate will increase